2020
DOI: 10.1136/bmjopen-2020-038153
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a progestin-primed ovarian stimulation protocol with a flexible GnRH antagonist protocol in patients with polycystic ovary syndrome who are participating in an IVF programme: study protocol for a randomised controlled trial

Abstract: IntroductionWomen with polycystic ovary syndrome (PCOS) undergoing in vitro fertilization (IVF) protocols are typically characterised by an increased number of oocytes retrieved. The oocytes are often of poor quality, leading to lower pregnancy rates, higher miscarriage rates and an increased risk of developing ovarian hyperstimulation syndrome (OHSS). Since our previous preliminary study showed that a novel progestin-primed ovarian stimulation (PPOS) protocol blocked the luteinising hormone (LH) surge during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Previous studies reported that the IVF outcomes of patients with endometriosis were improved by pretreatment with DNG, and myo-inositol is of proven utility in those with PCOS [ 45 , 46 ]. Our centre also published some work in this field on the basis of a novel ovarian stimulation strategy named progestin primed ovarian stimulation (PPOS) [ 15 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that the IVF outcomes of patients with endometriosis were improved by pretreatment with DNG, and myo-inositol is of proven utility in those with PCOS [ 45 , 46 ]. Our centre also published some work in this field on the basis of a novel ovarian stimulation strategy named progestin primed ovarian stimulation (PPOS) [ 15 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, regarding the comparison of PPOS protocols and GnRH antagonist protocols, there are 11 studies, including four RCTs (20,22,26,27), two prospective studies (28,29) and five retrospective cohort studies (19,21,(30)(31)(32). The populations in these studies had different characteristics, including PCOS, POR, normal ovarian response and donor oocyte cycles.…”
Section: Comparisons With Other Reportsmentioning
confidence: 99%
“…There are a large number of randomized controlled, prospective and retrospective studies on GnRH antagonist regimens that fully prove the effectiveness and safety of these regimens (10)(11)(12)(13). Regarding the PPOS protocols, although it has not been applied for a long time, studies have shown that it can achieve exact effectiveness and safety in different populations (19)(20)(21)(22). However, due to the short application time of the protocols and the limited amount of data, the long-term safety of offspring deserves further study.…”
Section: Future Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated that PPOS is effective for suppressing premature LH surge and decreasing OHSS incidence when used in combination with a freeze-all strategy and a GnRH-agonist trigger [8]. Several randomised controlled trials (RCTs) have compared the number of oocytes retrieved and pregnancy outcomes, including clinical pregnancy and live birth rate, between progestin-mediated and GnRH antagonist protocols in patients with PCOS [9,10] and poor responders [11]. Although these trials have reported no signi cant differences between the protocols, RCT data regarding the use of PPOS in patients with infertility who have normal ovarian reserve are limited.…”
Section: Introductionmentioning
confidence: 99%